Pelvic Floor Muscle Training In Women Practicing High-impact Sports: A Systematic Review - Fukuda, Fernanda Sayuri; Arbieto, Eliane Regina Mendoza; Da Roza, Thuane; Luz, Soraia Cristina Tonon da (International Journal of Sports Medicine, 2023)
Urinary incontinence (UI) in female athletes can impair their quality-of-life (QoL) and reduce their participation in sports. This review aims to evaluate the effect of pelvic floor muscle training (PFMT) in treating UI in women participating in high-impact sports. Furthermore, to assess the influence of PFMT on pelvic floor muscles (PFM) function and the UI impact on their QoL. For this purpose, a systematic review of randomized controlled trials (RCTs) and non-RCTs was performed. An electronic search was conducted on PubMed, EMBASE, SciELO, and Scopus. The quality of evidence was assessed using the PEDro and ROBINS-I scales. The Consensus on Exercise Reporting Template (CERT) was used to assess the quality of PFMT protocols. All studies were available in full-text including incontinent female participants who are practitioners of high-impact sports, investigating PFMT vs control groups(inactive) or undergoing other treatments. Three RCTs and two non-RCTs (104 participants) were analyzed. PFMT provided a significant improvement in UI symptoms with a reduction in the frequency (n=3) and the amount of UI (n=5). PFM function was assessed in three studies, and two found improvement in maximal contraction and one in vaginal resting pressure in favor of PFMT. None of the two studies that assessed QoL found a difference after PFMT intervention.
Keywords: pelvic floor; pelvic floor disorders; physiotherapy; sports; women